Effect of inspiratory oxygen fraction and perfusion pressure on 3D functional structures during hypoxia and reoxygenation in isolated perfused pig heart - Rauh, Robert; Böhnert, Markus; Kessler, Manfred (Proceedings Volume 4241, Saratov Fall Meeting 2000: Optical Technologies in Biophysics and Medicine II, 2001)
Subcellular structures are mainly responsible for light scattering in tissue. Since these structures change their outer shape during hypoxia, backscattered light intensity should be useful in monitoring of tissue in hypoxic or ischemic situations. In a new model of isolated perfused pig heart we investigated the relation between three-dimensional functional structures caused by tissue light scattering and the perfusion pressure during reoxygenation after hypoxia. By use of EMPHO-Oxyscan we could see that there is a clear relation between the perfusion pressure and the level of 3D structures. At very low perfusion pressures there is a delay in recovery of myocardium. Increase in perfusion pressure accelerates the recovery. With functional 3D images created by use of EMPHO-Oxyscan, we now have an instrument for depicting these processes. This technique will be useful in clinical monitoring in cardiac surgery, intraoperative as well as postoperativ